2012
DOI: 10.2466/09.02.20.pr0.110.3.1007-1020
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Adaptive and Maladaptive Perfectionism with Turkish Almost Perfect Scale—Revised

Abstract: The present study examined the factor structure of the Turkish Almost Perfect Scale–Revised to identify adaptive and maladaptive perfectionists and non-perfectionists and examined whether the participants ( N = 383) in these groups differed on a measure of psychological distress. A confirmatory factor analysis of the Turkish Almost Perfect Scale–Revised yielded three subscales: High Standards, Order, and Discrepancy. A cluster analysis identified adaptive perfectionists, maladaptive perfectionists, and non-per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…These factors have generally been replicated in subsequent confirmatory factor analyses, including studies conducted with translated versions (Nakano, 2009;Wang et al, 2007). Administration of the APS-R to 383 undergraduates from Turkey also yielded a three-factor solution that supported the multidimensionality of the APS-R based on confirmatory factor analysis (Ulu et al, 2012). Mobley et al (2005) established similarly via a confirmatory factor analysis that the three-factor solution fit the data for a sample of 251 African American students and a sample of 314 European American students.…”
Section: Construct/factor Analyticmentioning
confidence: 91%
See 1 more Smart Citation
“…These factors have generally been replicated in subsequent confirmatory factor analyses, including studies conducted with translated versions (Nakano, 2009;Wang et al, 2007). Administration of the APS-R to 383 undergraduates from Turkey also yielded a three-factor solution that supported the multidimensionality of the APS-R based on confirmatory factor analysis (Ulu et al, 2012). Mobley et al (2005) established similarly via a confirmatory factor analysis that the three-factor solution fit the data for a sample of 251 African American students and a sample of 314 European American students.…”
Section: Construct/factor Analyticmentioning
confidence: 91%
“…Mobley, Slaney, and Rice (2005) evaluated a sample of 251 African American university students and reported alpha coefficients of .75 for high standards, .91 for order, and .88 for discrepancy. Ulu, Tezer, and Slaney (2012) found in a large sample of undergraduates from Turkey that alpha coefficients were .78 for high standards, .85 for discrepancy, and .86 for order. Alpha coefficients reported for a sample of Japanese students were .81 for high standards, .90 for discrepancy, and .73 for order (Nakano, 2009).…”
Section: Internal Consistencymentioning
confidence: 95%
“…In addition to these two models, Slaney et al (2001) studied perfectionism both qualitatively and quantitatively and they concluded that perfectionism is manifested in a three dimensional way including setting high standards, being orderly and having discrepancy in standards and performance. On the basis of their findings, they developed Almost Perfect Scale-R in 2001 and proposed that adaptive perfectionist set high standards for themselves and are more orderly and have low discrepancy between goals and performance while maladaptive perfectionist have high standards, are low in orderliness and have high discrepancy (Ulu & Tezeg, 2012). The current research focuses on the three dimensional presentation of perfectionism proposed by Slaney and colleagues and exploring what role perfectionism is playing in burnout in the presence of worry and rumination.…”
mentioning
confidence: 99%
“…The validity of the APS-R has been explored in several culturally diverse populations, and translated to various languages including Chinese, Asian, Indian, African American, and Turkish samples (e.g., Aydin;2013;Yang et al, 2007;Mobley, Slaney, & Rice, 2005;Slaney, Chadha, Mobley, & Kennedy, 2000;Slaney, Mobley, Trippi, Ashby, & Johnson, 1996;Ulu, 2007;Ulu, Tezer, & Slaney, 2012;Wang, Puri, Slaney, Methikalam, & Chadha, 2012;Wang, Slaney, & Rice, 2007;Wang, Yuen, & Slaney, 2009). Further, a short version of the scale that includes 8 of its items and represents standards and the discrepancy was tested and found to have similar characteristics (Rice, Richardson, & Tueller, 2014).…”
Section: Kira Et Al Psychologymentioning
confidence: 99%